Exploring good practice in life story work with people with dementia: The findings of a qualitative study looking at the multiple views of stakeholders. (February 2020) - Gridley, Kate; Birks, Yvonne; Parker, Gillian
Introduction: Despite growing international interest in life story work as a tool for person-centred dementia care, there is little agreement on what constitutes good practice and little evidence from the perspectives of people with dementia or their family carers. Design and methods: This paper reports the findings from the qualitative element of a larger study looking at the feasibility of evaluating life story work. Ten focus groups were held with 73 participants: four groups of people with dementia (25 participants); three with family carers (21 participants); and three with staff, professionals and volunteers with experience of life story work (27 participants). Findings: It became apparent through our focus groups that, when people talk about 'life story work', different people mean different things. This related to both process and outcomes. In particular, a person with dementia may have very different views from others about what life story work is for and how their life story products should be used. There was general agreement that a good practice approach would be tailored to the individual needs and preferences of the person with dementia. However, in practice many settings used templates and the process was led by staff or completed by family carers. Conclusion: We produced nine key features of good practice which could be used to guide the life story work process. Key elements include the recognition that not everyone will want to take part in life story work and that some people may even find it distressing; the importance of being led by the person with dementia themselves; the need for training and support for staff, carers and volunteers; and the potential for life story work to celebrate the person's life today and look to the future.